2002
DOI: 10.1152/japplphysiol.00105.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of skin blood flow and sweating rate in exercise thermoregulation after bed rest

Abstract: Two potential mechanisms, reduced skin blood flow (SBF) and sweating rate (SR), may be responsible for elevated intestinal temperature (T(in)) during exercise after bed rest and spaceflight. Seven men underwent 13 days of 6 degrees head-down bed rest. Pre- and post-bed rest, subjects completed supine submaximal cycle ergometry (20 min at 40% and 20 min at 65% of pre-bed rest supine peak exercise capacity) in a thermoneutral room. After bed rest, T(in) was elevated at rest (+0.31 +/- 0.12 degrees C) and at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 33 publications
5
40
2
Order By: Relevance
“…The gain of the V _ O 2 /D Tre response is attenuated in the Post-bedrest trial, reflecting an attenuation of shivering thermogenesis would be less prominent, due to the fairly rapid recovery of plasma volume following the cessation of bed-rest (Fortney et al 1991). Our findings are in agreement with those of Greenleaf and Reese (1980) and Lee et al (2002), who reported no effects of bed-rest on the gain and magnitude of the sweating response after 14 days of bed-rest. In contrast to Lee et al (2002), who noted a delay in the onset of the sweating response, we did not observe such a shift in the core temperature threshold for onset of sweating.…”
Section: Exercise Temperature Regulationsupporting
confidence: 93%
See 2 more Smart Citations
“…The gain of the V _ O 2 /D Tre response is attenuated in the Post-bedrest trial, reflecting an attenuation of shivering thermogenesis would be less prominent, due to the fairly rapid recovery of plasma volume following the cessation of bed-rest (Fortney et al 1991). Our findings are in agreement with those of Greenleaf and Reese (1980) and Lee et al (2002), who reported no effects of bed-rest on the gain and magnitude of the sweating response after 14 days of bed-rest. In contrast to Lee et al (2002), who noted a delay in the onset of the sweating response, we did not observe such a shift in the core temperature threshold for onset of sweating.…”
Section: Exercise Temperature Regulationsupporting
confidence: 93%
“…Our findings are in agreement with those of Greenleaf and Reese (1980) and Lee et al (2002), who reported no effects of bed-rest on the gain and magnitude of the sweating response after 14 days of bed-rest. In contrast to Lee et al (2002), who noted a delay in the onset of the sweating response, we did not observe such a shift in the core temperature threshold for onset of sweating.…”
Section: Exercise Temperature Regulationsupporting
confidence: 93%
See 1 more Smart Citation
“…This team studied maximal forearm cutaneous vascular conductance (plethysmography) and sweat gland function (acetylcholine intradermal microdialysis) during a 14-day HDBR. Lee et al (2002) suggest a centrally mediated elevation in the thermoregulatory set point during bed rest exposure.…”
Section: Decrease In Exercise Capacitymentioning
confidence: 90%
“…For example, reduced endothelium-mediated vasodilatory responses have been reported in vivo (65) and in vitro (12,13,25,33,55,65,71) after hindlimb unloading in rats. In addition, reduced dilation has been reported in the vasculatures of the forearm in patients on bed rest (10,11,29,57) and in astronauts after long-term spaceflight (17). We and others (25,55,65) have hypothesized that reduced NO dilation may contribute to attenuated exerciseinduced skeletal muscle vasodilation and reduced exercise capacity observed after hindlimb unloading (14, 46, 64) and , and systemic NOS (20 mg/kg L-NAME) in control (n ϭ 8) and HU rats (n ϭ 6).…”
Section: Discussionmentioning
confidence: 99%